2015
DOI: 10.1111/jsm.12728
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Postoperative Hematoma Formation After Inflatable Penile Prosthesis Implantation

Abstract: Introduction Infrequent but serious postoperative complications following inflatable penile prosthesis (IPP) insertion include infection, malfunction, and bleeding. Although prior publications report methods to reduce immediate postoperative bleeding, there is little in the literature concerning the etiology, diagnosis, imaging, and management of delayed bleeding after IPP insertion. Aim The aim of the study was to review cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Drain placement has not been associated with increased risk of infection ( 39 ). Garber and Bickell ( 40 ) reported a delayed hematoma rate of 0.5% that occurred during the second postoperative week; onset was associated with excessive physical activity and premature use of anticoagulants. The rate of hematoma at 18 months follow up has been estimated at 0.7% ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drain placement has not been associated with increased risk of infection ( 39 ). Garber and Bickell ( 40 ) reported a delayed hematoma rate of 0.5% that occurred during the second postoperative week; onset was associated with excessive physical activity and premature use of anticoagulants. The rate of hematoma at 18 months follow up has been estimated at 0.7% ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pozza and colleagues examined hematoma formation in the immediate post-operative period (post-operative day one) for semi-rigid and inflatable prostheses with and without scrotal drainage ( 34 ). Another study reviewed delayed hematoma formation defined as occurrence after the fifth post-operative day ( 38 ). This study purported to be the only focusing on delayed hematoma formation.…”
Section: Bleeding and Hematomamentioning
confidence: 99%
“…Post-operative scrotal hematoma in the setting of penile prosthesis implantation is often managed expectantly without further surgical intervention. Conservative management includes a combination of bed rest, scrotal elevation, compression dressing, ice application, and antibiotics ( 38 , 45 ). In one large retrospective study of 955 penile prosthesis implantations, Chung and colleagues reported that penoscrotal bruising was a common occurrence without quantification of frequency, but they did report that none of the hematomas required surgical intervention ( 33 ).…”
Section: Bleeding and Hematomamentioning
confidence: 99%
See 1 more Smart Citation
“…Other complications involve the reaction of the tissues affected by the implant, with the development of oedema, lymphangitis (10), scrotal effusion, serous and bloody effusion (11,12),local and regional hyposensitivity, reduced shaft size and urinary problems, which may require further surgery, with no guarantee of success.…”
Section: Introductionmentioning
confidence: 99%